2000
DOI: 10.1046/j.1365-3083.2000.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, B, Cw and DRB1, DRB3/4/5, DQB1, DPB1 Frequencies in German Immunoglobulin A‐Deficient Individuals

Abstract: HLA class I and II frequencies and haplotype frequencies were determined in 80 German immunoglobulin (Ig)A‐deficient individuals and 157 healthy controls with normal IgA levels using serological and DNA typing methods. For several alleles, significant associations were found, which could be explained mainly in the context of a positive association with three different extended haplotypes (HLA‐B*08:DRB1*0301: DQB1*0201, HLA‐B*14:DRB1*0102:DQB1*0501 and HLA‐B*44:DRB1*0701:DQB1*0202) and a negative association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Of 26 homozygous probands, only a single case exhibited homozygosity in the telomeric part of the class III region and not in the HLA-DQ/DR region. The frequencies of unaffected homozygous individuals (7.7% for 4-STRs and 5.9% for 5-STRs) were comparable to ϳ6 -8% homozygosity observed in large numbers of population controls typed for HLA-DR or -DQ specificities (38,39).…”
Section: Homozygosity At Hla-dq/drsupporting
confidence: 64%
See 1 more Smart Citation
“…Of 26 homozygous probands, only a single case exhibited homozygosity in the telomeric part of the class III region and not in the HLA-DQ/DR region. The frequencies of unaffected homozygous individuals (7.7% for 4-STRs and 5.9% for 5-STRs) were comparable to ϳ6 -8% homozygosity observed in large numbers of population controls typed for HLA-DR or -DQ specificities (38,39).…”
Section: Homozygosity At Hla-dq/drsupporting
confidence: 64%
“…Because previous association studies suggested an increase of homozygosity in affected individuals vs controls both for HLA-DQ/DR (38,39) and HLA STRs (21), we estimated the relative risk of IgAD/CVID conferred by homozygous stretches at adjacent STRs and examined which region was associated with the highest risk. We chose to test 4-and 5-STR sliding windows because the average probability of being homozygous by chance was sufficiently low (ϳ2 ϫ 10 Ϫ3 and 3 ϫ 10 Ϫ4 , respectively), minimizing random homozygosity at adjacent STRs.…”
Section: Homozygosity At Hla-dq/drmentioning
confidence: 99%
“…Homozygosity for the ancestral 8.1 haplotype increases the risk of development of the disease even further (10). Other haplotypes, including HLA-DR7, DQ2 and DR1, DQ5 are also associated with IgAD (11). In contrast, the DR15, DQ6 haplotype has been shown to confer an almost complete protection against the disorder (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies support a polygenic inheritance with a susceptibility locus (designated IGAD1) in the MHC. Associations of IgAD were first described with HLA class I alleles, most consistently with A1 and B8 (2-4) but also with A28, B14 (5-7), and B44 (8,9). Subsequently, an association with the class II allele HLA-DR3 was repeatedly observed (4, 9 -14), in addition to associations with DR1 (7, 9 -11) and DR7 (6,9,10,12).…”
mentioning
confidence: 95%
“…Associations of IgAD were first described with HLA class I alleles, most consistently with A1 and B8 (2-4) but also with A28, B14 (5-7), and B44 (8,9). Subsequently, an association with the class II allele HLA-DR3 was repeatedly observed (4, 9 -14), in addition to associations with DR1 (7, 9 -11) and DR7 (6,9,10,12). Some early studies already signaled that the association was with particular combinations of MHC alleles rather than with individual alleles per se (5,7) and that these combinations reflected extended, conserved, or "ancestral" haplotypes A1-B8-DR3, A28-B14-DR1, and B44-DR7 (7,8,11,15).…”
mentioning
confidence: 99%